The edge of the shadows - George, Elizabeth, 1949- (Whidbey Island saga, 2015)
The first fire may have been an accident, but what about the second? And the third-- the one that killed someone. Becca King and her friends wonder if one of the newcomers to the island is to blame. Perhaps it's Isis Martin's brother, Aidan, just home from a school for troubled teens. Or Parker Natalia, a talented musician fired by his bandmates for unknown reasons. Fellow psychic Diana Kinsale encourages Becca to explore her growing extrasensory abilities. Beautiful Whidbey Island may seem like a tranquil haven, but all is not as it seems.